2010
DOI: 10.1186/1743-7075-7-80
|View full text |Cite
|
Sign up to set email alerts
|

Effects of olive oil and its fractions on oxidative stress and the liver's fatty acid composition in 2,4-Dichlorophenoxyacetic acid-treated rats

Abstract: BackgroundOlive oil's beneficial effects are not only related to its high content of oleic acid, but also to the antioxidant potential of its polyphenols. In this study, we assess the effects of virgin olive oil and its fractions on 2,4-D- induced oxidative damage in the liver of rats.MethodsMale Wistar rats were randomly divided into eight groups of ten each: (C) a control group, (D) group that received 2,4-D (5 mg/kg b.w.), (D/EVOO) group treated with 2,4-D plus extra virgin olive oil, (D/OOHF) group that re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
38
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 58 publications
(41 citation statements)
references
References 56 publications
2
38
0
1
Order By: Relevance
“…Nakbi et al (27) concluded that protective effect of oleic acid against oxidative damage (26). These findings clarifies that how a high-fat diet protects the liver in our study.…”
supporting
confidence: 77%
See 1 more Smart Citation
“…Nakbi et al (27) concluded that protective effect of oleic acid against oxidative damage (26). These findings clarifies that how a high-fat diet protects the liver in our study.…”
supporting
confidence: 77%
“…Gomez-Lechona et al (28), designed a study to define an experimental model of hepatocellular steatosis, and found that a high proportion of palmitic acid (oleate/ palmitate, 0:3 ratio) might represent a cellular model of steatosis (27).…”
mentioning
confidence: 99%
“…Results were in accordance to previous works on other bamboo species (Goyal et al 2011a;Nagavani and Rao 2010). Mostly, the antioxidant activity in plants is due to the presence of polyphenols (Nakbi et al 2010;Middha et al 2013;Usha et al 2014). Moreover, the higher the inhibitory action, the more powerful is the antioxidant activity (Ajith 2010).…”
Section: Ferric Reducing Power Assay (Frap)mentioning
confidence: 99%
“…Extra virgin olive oil and its fractions analysis were performed as reported in our previous paper [27]. In fact, the determination of fatty acids was accomplished through the quantification of their methyl esters (FAMEs) by gas chromatography using a model 5890 series II instruments (HewelettPackard Ca Palo Alto, California, USA) as described in ref.…”
Section: Oil Sample Analysismentioning
confidence: 99%
“…The olive oil lipophilic fraction (OOLF) was obtained from EVOO as follows: the EVOO was homogenized for 1 min with water (1:1, v/v), and the oil was separated by centrifugation; this procedure was repeated six times. Then, the oil fraction (OOLF) was filtered through a cellulose acetate membrane [26,27].…”
Section: Oil Sample Analysismentioning
confidence: 99%